Case Study : Julie's Manufacturing Sdn. Bhd. (Su Chin Hock) / Muhamad Syamir Saifulizan - Saifulizan, Muhamad Syamir (2021)
Alhamdulillah all praises to ALLAH S.W.T because with His grace I can complete the task given in the time that has been set and be able to produce it with high quality. I would also like to express my highest appreciation to my lecturer, Nur Hazelen binti Mat Rusok who is willing to teach me so that I can produce this individual assignment. This research was made by me focusing on Julie's Manufacturing Sdn. Bhd. The company was founded in the year 1981. It is one of the successful biscuit company in Malaysia. The company felt into category Small and Medium Enterprises (SME) with over 1000 employees. The founder, Su Chin Hock has overcome many difficulties and challenges to survive for this 35 years. Some of the challenges almost tainted the good name of Julie's Manufacturing Sdn. Bhd. but with sharp intuition and quick thinking of the founder, the company remain operating and still stand until now. This research will elaborate more on the company background, founder and current owner. Next, data collections method that I use is by searching via internet. The data in this research are valid and correct. Unfortunately for me I cannot run an interview session with one of Julie's Manufacturing Sdn. Bhd. employees' because of the global pandemic that arises has affected type of learning from face to face to Online Distance Learning (ODL). Thus, every unnecessary movement will be limited including travelling interstate without having a solid reasons. Last but not least, in this research will explain more about Julie’s Manufacturing Sdn. Bhd. core competencies'. Core competencies are the instruments and skills that make up a company's competitive advantages. To strive against the competition, a company must identify, develop, and optimize its core competencies according to suitable management. The core competencies is important to keep the company operating. Core competencies also plays a major role in solving problem that arise in or within the company. The core competencies mention above is passion, integrity, conscience, accountability and more. I hope the results of the research that I have done are clear and easy to understand. I also hope that this study will be able to answer the questions that arise on the Julie’s Manufacturing Sdn. Bhd. This research are suitable for any types of society.